Managing selected production level complexities and outcomes in block caving - Kamp, C (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Block caving performance is strongly dependent on adherence to fundamental caving principles applied consistently in both space and time. Sequencing and timing are as important as the activities themselves, and deviations driven by production pressure can lead to increased cave related risks and long-term impacts to reserve recovery. This paper discusses selected operational complexities encountered across several caving stages, drawing on industry experience and from New Afton Mine. Specific solutions are broadly presented for undercut swell management, remnant pillar recovery, drawbell blast underbreak, oversize and mudrush management, convergence and draw control, and the re-opening of collapsed drawpoints including checkerboarding and load shedding strategies. In several cases the methods go beyond what is typically found in generic design guidelines. A detailed case study of drawpoint grade performance following convergence and re-opening events in the Lift 1 east cave is then presented. Severe convergence drawpoints delivered a median grade reduction of 34% on Au and 31% on Cu in the 5 months following re-opening, with a 2013 pre-mining personal computer block cave (PCBC) forecast and a 2022 post-reconciliation PCBC model over-predicting actual grade across the majority of the observable height of draw (HOD) range. A mechanism hypothesis is proposed to explain the observed post-reopen grade behaviour, supported by field observations, geotechnical monitoring data and an additional PCBC run in which the draw columns of severely converged drawpoints were narrowed above their HOD at closure. This narrowing reduced the divergence between modelled and actual grade for the majority of severe drawpoints assessed and identified the HOD at closure as a physically meaningful threshold for the onset of draw column narrowing. The findings demonstrate that the grade impacts of severe convergence on the extraction level persist well beyond rehabilitation and are not readily captured by standard draw scheduling assumptions but, can be reproduced by representing the converged ore column as a narrowed draw cone.
Keywords: draw control